Nature and its symbols - Impelluso, Lucia; J. Paul Getty Museum (Los Angeles : J.P. Getty Museum, 2004)
"The Guide to Imagery series introduces readers to important visual vocabulary of Western art."-back cover.
Plants --Flowers --Fruits --Land animals --Flying animals --Aquatic animals --Creatures of the imagination.
Includes indexes.
Keywords: Plants in art; Animals in art; Symbolism in art; Art -- Themes, motives